2014
DOI: 10.1172/jci71856
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal delivery of a double-stapled RSV peptide prevents nasopulmonary infection

Abstract: Respiratory syncytial virus (RSV) infection accounts for approximately 64 million cases of respiratory disease and 200,000 deaths worldwide each year, yet no broadly effective prophylactic or treatment regimen is available. RSV deploys paired, self-associating, heptad repeat domains of its fusion protein, RSV-F, to form a fusogenic 6-helix bundle that enables the virus to penetrate the host cell membrane. Here, we developed hydrocarbon double-stapled RSV fusion peptides that exhibit stabilized α-helical struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 46 publications
0
70
3
1
Order By: Relevance
“…A similar strategy of i.n. peptide delivery has recently been proposed for preventing the spread of respiratory syncytial virus infection to the lung (96), suggesting that this approach may be extended to other respiratory infections. The efficacy of i.n.…”
Section: Discussionmentioning
confidence: 99%
“…A similar strategy of i.n. peptide delivery has recently been proposed for preventing the spread of respiratory syncytial virus infection to the lung (96), suggesting that this approach may be extended to other respiratory infections. The efficacy of i.n.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the therapeutic potential of hydrocarbonstapled peptides in the treatment of cancer, specifically by inhibiting the NOTCH transcription factor complex [25], reactivating the p53 tumour suppressor pathway [39][40][41][42], and promoting B cell lymphoma 2 (Bcl-2)-mediated apoptosis [43]. They have also shown potential as therapeutic agents for various other diseases, such as HIV [44,45], diabetes [46], cardiovascular disease [47], and respiratory infection [48]. Two hydrocarbon-stapled peptides developed by Aileron Therapeutics are currently undergoing clinical trials for the treatment of orphan endocrine disorders and malignant tumours [49].…”
Section: Hydrocarbon Staplesmentioning
confidence: 99%
“…These doubly stapled peptides demonstrated comparable binding affinity and enhanced proteolytic stability relative to the equivalent singly stapled peptide. A fusion peptide derived from the respiratory syncytial virus and stabilised by two i, i + 7 staples was also found to be exceptionally protease resistant and highly effective in suppressing viral infection in mouse models [48].…”
Section: Multiple Staplesmentioning
confidence: 99%
“…By sampling alternative staple positions, interrogating cellular uptake, and correlating biochemical function with antitumor activity and mechanism of action, we have generated lead compounds that form the basis for therapeutic development (16,17,19,20). Here, we report the application of all-hydrocarbon stapling to recapitulate the native primary sequence and secondary structure of the RAS-interacting α-helix of SOS1.…”
mentioning
confidence: 99%